DISCRIMINATION OF EYES WITH PRIMARY OPEN-ANGLE GLAUCOMA FROM NORMAL USING MACULAR GC-IPL THICKNESS - VIRANI, ANJALI; KHARE, PRAVEEN; PATEL, UMESH KUMAR; SINGH, PUJA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Primary open-angle glaucoma (POAG), a neuro-ophthalmological disease, is a condition of slowly progressive loss of retinal ganglion cells which are evident as characteristic optic nerve head vicissitudes and visual field defects, only after death of more than 40% of cells. This huge loss when witnessed is started to treat only if the patient approaches an ophthalmologist with a significant complaint, leading to optic nerve head examination, which means being an asymptomatic disease, it is usually left undiagnosed until advanced. An additional system of diagnosis of the disease earlier in the stage can aid reduce the burden of the blindness of POAG. Methods: Among a total of 62 eyes of 31 subjects, 40 eyes of 20 POAG subjects, and 22 eyes of 11 age-matched healthy subjects were recruited. All of them underwent Spectral Domain Optical Coherence Tomography macular and optic disk scans to note macular ganglion cell–inner plexiform layer (mGCIPL) and retinal nerve fiber layer (RNFL) thicknesses. Statistical analysis was did using an unpaired t-test and calculating a two-tailed p value, in which the significance was indicated by p<0.05. Results: Similar to peripapillary RNFL thickness, the mGCIPL parameters, that is, minimum GCIPL thickness and GCIPL thickness in all sectors decreased significantly in POAG eyes to be able to discriminate them from normal. mGCIPL and RNFL thickness decreased as the severity of glaucoma increased. Conclusion: The minimum GCIPL thickness and that in all sectors can discriminate POAG eyes from healthy eyes significantly and has comparable performance to that of peripapillary RNFL thickness.